Análisis de enfoques pedagógicos en el proceso enseñanza - aprendizaje de las actividades deportivas extracurriculares del colegio La Condamine ubicado en Quito en el periodo escolar 2014 - 2015 - Rivera Molina, María Marisol (2015)
Extracurricular activities are activities that are performed outside of regular school hours. These activities seek to provide young people and teen agers comprehensive education and the time occupation appropriate for training. The formation provides students not only results academics, also the young people and teen agers are related with the encouragement of physical and social skills. In the present study addresses extracurricular sports activities in order to establish a concordance, which provides the institution with the requirements of the Ministry of Education. This study was conducted a literature review of documents issued by the Ministry of Education concerning the formation of extracurricular activities, curriculum updates in the area of physical education, has also review pedagogical approach curricular valid in Ecuadorian law, pedagogical approaches existing in the French education, specific documentation of the institution and finally the interests and the use of leisure time of youth and teenagers. We performed a study with qualitative and exploratory approach, has worked with the entire sample of instructors and the entire student sample that makes sports workshops. Likewise, conducted two surveys: one directed at instructors to collect information concerning pedagogical approaches used, information on strategies to promote learning and assessment of learning. The other survey is aimed at students to know their interests when making extracurricular sports activities and also know the external advocacy for the election of a workshop.